Operationalisng Sustainable Development Goal (SDG) 4 in Nigeria: Artificial Intelligence and Employability of Graduates (2020)
Man's deficiency at applying acquired knowledge intelligently has prompted development of Artificial Intelligence (A.I.), a computer device designed to learn new concepts and tasks; it also possesses the ability to reason and draw conclusions about the world. This shows that man finds it difficult to articulate and stimulate knowledge appropriately which affected development. Products of educational institutions particularly in Nigeria have not been found employable. Man and his nature support acquisition of knowledge. However, intelligent application of this knowledge had been queried severally. Can it be claimed that human nature negates positive application of knowledge for the purpose of development? This paper expounded the concepts of human nature, Artificial Intelligence, employability, and education in relation to operationalising United Nation's Sustainable Development Goal (SDG) 4. The paper employed the speculative, historical, analytic and prescriptive methods, and concluded that operationalising the SDG 4 has become imperative, therefore, every means must be utilised to ensure its success through the process of education. The paper therefore recommended that teachers should discard the 'banking' method of teaching and develop learners said that they are allowed to discover knowledge and endeavour to apply same intelligently with the government providing appropriate environment for education and its process to thrive.